Evaluación a la ejecución presupuestaria de los gobiernos autónomos descentralizados parroquiales rurales de Aláquez y Panzaleo de los años 2019 y 2020 - Rivera Berrazueta, Erika Paola (2022)
The present work entitled "Evaluation of the Budgetary Execution of the Decentralized Autonomous Rural Parochial Governments of Aláquez and Panzaleo for the years 2019 and 2020" had the objective of describing the budgetary administration of the Decentralized Autonomous Rural Parochial Governments from different approaches and perspectives; to carry out a situational analysis on the budget execution of the Decentralized Autonomous Rural Parochial Governments in the Province of Cotopaxi and to quantify through indicators the budget execution of the Decentralized Autonomous Rural Parochial Governments of Aláquez and Panzaleo for the years 2019 and 2020. A field work of deductive research type was carried out, starting from the governmental regulations to comply with, the use of the FODA tool that allowed the situational diagnosis and the analysis on the budget cycle of the public institutions, with which it was evaluated the most of the Decentralized Autonomous Rural Parochial Governments upload budgetary information to their websites but not the evaluation of compliance and achievements of planned expenditures, investments and constructions. It is recommended to explain the methodology and instruments used in the research to the managers and financial personnel of the Decentralized Autonomous Rural Parochial Governments of the province of Cotopaxi to promote budgetary evaluation reports and subsequent publication on their institutional websites.